Menggeliatnya Bisnis Dan Investasi Properti Di Surakarta - Paningrum, Destina (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2013)
In this moment , property investment be the favourite for businessman as considered safelyand promising for bright prospects in Surakarta. Moreover, the property segment in Indonesia highly open wide, both for Investment and Business. Shopping center, home property that can be a golden opportunity to invest in lucrative property. The demographic layout is located in the city of Surakarta, Central Java province , Indonesia. The population of 503.421 inhabitants (2010 ) and the density of 13.636 inhabitants / km2 Where size 44 km2 city that around Karanganyar And Boyolali in northside, Karanganyar and Sukoharjo in next east and west, and Sukoharjo in the south, Its Business Property can be highly profitable, because so many newcomers settled in Surakarta. The Business is growing. In Surakarta malls or shopping center which also adds to the advance of property in Surakarta.Keywords :Property Investement, Demography of Surakarta, Profit and Loss Business of Property in Surakarta